Salivary Protein 1 of Brown Planthopper Is Required for Survival and Induces Immunity Response in Plants - Huang, Jin; Zhang, Ning; Shan, Junhan; Peng, Yaxin; Guo, Jianping; Zhou, Cong; Shi, Shaojie; Zheng, Xiaohong; Wu, Di; Guan, Wei; Yang, Ke; Du, Bo; et al. (Frontiers in Plant Science, 2020)
The brown planthopper (BPH), Nilaparvata lugens Stål, is one of the major pests of rice. It uses its stylet to penetrate rice phloem, feeding on rice sap and causing direct damage to rice or even plant death. During the feeding process, BPHs secrete saliva into plant tissues, which plays crucial roles in the plant-insect interactions. However, little is known about how the salivary proteins secreted by BPH affect feeding ability and how they induce plant immune responses. Here, we identified an N. lugens Salivary Protein 1 (NlSP1) by screening salivary proteome and characterized its functions in BPH and plants. NlSP1 induces cell death, H2O2 accumulation, the expression of defense-related genes, and callose deposition in planta. The active region of NlSP1 that induces plant cell death is located in its N-terminal region. Inhibition of NlSP1 expression in BPHs reduced their feeding ability and had a lethal effect on them. Most importantly, we demonstrated that NlSP1 was able to be secreted into rice plant during feeding process and form a complex with certain interacting partner of rice. These results provide a detailed characterization of a salivary protein from BPHs and offers new insights into our understanding of rice-BPH interaction.